Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.polymdegradstab.2009.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relationships of new polystyrene nanocomposites prepared from initiator-containing layered double hydroxides of zinc aluminum and magnesium aluminum

Abstract: This paper is NOT THE PUBLISHED VERSION; but the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in the citation below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 36 publications
1
29
0
3
Order By: Relevance
“…Basicamente este fato se deve à interação entre o polímero e as lamelas do HDL, onde temos monolamelas com dimensões nanométricas criando uma grande área superficial de contato entre HDL e poliestireno, o que acarreta a formação de ligações mais fortes e em maior número, possibilitando que ocorra um completo sinergismo entre matriz e reforço. Com esta interação entre reforço e matriz, este material apresenta uma maior resistência à difusão de oxigênio e compostos voláteis, outro fato de extrema importância para degradação mais lenta [16][17][18][19] . Na análise de TGA para os nanocompósitos é possível verificar um primeiro passo de degradação com valores de 130 a 220 °C, principalmente nos nanocompósitos com 3 e 5% de HDL, os com 0,5 e 1% essa degradação é muito sutil.…”
Section: Análise De Metunclassified
“…Basicamente este fato se deve à interação entre o polímero e as lamelas do HDL, onde temos monolamelas com dimensões nanométricas criando uma grande área superficial de contato entre HDL e poliestireno, o que acarreta a formação de ligações mais fortes e em maior número, possibilitando que ocorra um completo sinergismo entre matriz e reforço. Com esta interação entre reforço e matriz, este material apresenta uma maior resistência à difusão de oxigênio e compostos voláteis, outro fato de extrema importância para degradação mais lenta [16][17][18][19] . Na análise de TGA para os nanocompósitos é possível verificar um primeiro passo de degradação com valores de 130 a 220 °C, principalmente nos nanocompósitos com 3 e 5% de HDL, os com 0,5 e 1% essa degradação é muito sutil.…”
Section: Análise De Metunclassified
“…The reduction in PHRR is important for fire safety, as PHRR represents the point in a fire where heat is likely to propagate further, or ignite adjacent objects. [31] The HRR plots for pure PLA and its nanocomposites are shown in Fig. 7.…”
Section: Thermal Analysis (Dsc)mentioning
confidence: 99%
“…The shape of the TGA curve for the LDHs nanocomposites was very similar to that of the parent polymer, although T 0.1 and T 0.5 were slightly lower. This is probably due to the presence of LDH, which starts to decompose at a lower temperature [26,40]. The weight loss of the nanocomposites below 250 8C can be attributed to the loss of physical absorbed water (<150 8C) and interlayer water (150-250 8C) [19].…”
Section: Thermal Propertymentioning
confidence: 99%
“…In recent years, the intercalated or exfoliated polymer/LDH nanocomposites [17][18][19][20][21], especially PS/LDH nanocomposites [22][23][24][25][26] have attracted great interest in the field of material science due to their excellent thermal stability, flame retardancy, and physicochemical properties. Gao et al [9] reported the flame retardancy and rheological properties of high density polyethylene nanocomposites filled with different inorganic ions.…”
Section: Introductionmentioning
confidence: 99%